Effect of the Selected Balance Program on Postural Control of Amputees under Manipulation of Visual, Vestibular and Proprioceptive Systems - B. Mohamadtaghi B.; P. Hejazi Dinan; P. Shamsipour Dehkordi (Afarand Scholarly Publishing Institute, 2016)
Aims: Exercise therapy intervening methods are used by physical medicine and rehabilitation therapists to increase the capability to keep balance and independent functioning in the lower limb amputees. The aim of this study was to investigate the effects of the selective balance program on postural control in the lower limb amputees under manipulation of visual, vestibular, and proprioceptive sensory systems.     Materials & Methods: In the semi-experimental study, 14 amputees with under the knee amputation referred to Tehran Red Crescent Rehabilitation Center were studied in .... The subjects selected via available sampling method were divided into two 7-person groups including "control" and "selective postural" groups. Sensory organization test was used to assess postural control and balance of the subjects by computerized dynamic posturography system. Data was analyzed by SPSS 19 software using composed factor ANOVA with repeated measures and Bonferroni post-hoc test.   Findings: There was an increase in the balance and postural control in the posttest step in exercise therapy group than control group. In the posttest step in postural group, alignment and strategy scores of the first (presence of visual, vestibular, and proprioceptive senses) and the second (elimination of vision and manipulation of vestibular and proprioceptive senses) situations were higher than other situations, while the score of displacement of the center of gravity in the mentioned situations was less than other situations. In the posttest step in postural group, postural and strategy scores and the score of displacement of the center of gravity in the sixth (manipulation of vestibular and proprioceptive senses) situation were less and higher than other situations, respectively.   Conclusion: A course of selective exercise therapy program leads to a reduction in the displacement amplitude and an enhancement in alignment, as well as an increase in strategy, in persons with under the knee amputation, showing increases in balance and postural control.